Frontline social service as a battlefield: Insights from street‐level bureaucrats' interactions with violent clients. (12th July 2021) - Davidovitz, Maayan; Cohen, Nissim
Abstract: How do different types of social service providers experience and respond to violent clients? The street‐level social service environment is a fertile ground for manifestations of violence by dissatisfied clients. This study examines the violence, verbal, and physical, to which street‐level bureaucrats are exposed, and the different coping strategies they adopt. We explore these issues using interviews with 71 Israeli social service providers. Our results indicate that while some street‐level bureaucrats are tolerant of client violence, others refuse to accept it. The former weigh their words, express empathy and seek to satisfy demands. The latter recruit the support of additional players and server relationships.